Lived-in experiences of health care professionals affected with COVID-19 - Radhakrishnan Govindan; Sailaxmi Gandhi; Prasanthi Nattala; Bingi Rajeswari (Indian Journal of Psychiatry)
Background and Objective: Healthcare providers (HCPs) were vital during the COVID-19 pandemic. The healthcare providers affected by COVID-19 underwent various life changing events while continuing their profession during the pandemic. This study is aimed to explore the lived-in experiences of HCPs affected by COVID-19 at a tertiary care Mental Health Institute in India. Materials and Methods: The sampling method was purposive. Twenty two HCPs (eight nursing educators, seven nursing officers, five contractual cleaning workers, and two laboratory technicians) participated in the interviews conducted by the researchers to obtain the lived-in experiences of HCPs who have recovered from COVID-19. Researchers used a sociodemographic form and an interview guide to collect the data. Interviews were audio recorded and analyzed by using Atlas-ti-9 software. Results: All the participants were female, and they revealed various physical, psychological, and social issues faced by HCPs while balancing home and workplace. Thematic data analysis resulted in the emergence of two themes and 11 subthemes related to life changing events. Conclusion: The findings concluded that although the healthcare providers had working experience in the field of mental health, they too experienced mild psychological issues like anxiety, depression, and fear of death because of this pandemic situation.